Human‐modified habitats change patterns of population genetic structure and group relatedness in Peter's tent‐roosting bats. Issue 17 (29th July 2016) - Sagot, Maria; Phillips, Caleb D.; Baker, Robert J.; Stevens, Richard D.
Abstract: Although coloniality is widespread among mammals, it is still not clear what factors influence composition of social groups. As animals need to adapt to multiple habitat and environmental conditions throughout their range, variation in group composition should be influenced by adaptive adjustment to different ecological factors. Relevant to anthropogenic disturbance, increased habitat modification by humans can alter species' presence, density, and population structure. Therefore, it is important to understand the consequences of changes to landscape composition, in particular how habitat modification affects social structure of group‐forming organisms. Here, we combine information on roosting associations with genetic structure of Peter's tent‐roosting bats, Uroderma bilobatum to address how different habitat characteristics at different scales affect structure of social groups. By dividing analyses by age and sex, we determined that genetic structure was greater for adult females than adult males or offspring. Habitat variables explained 80% of the variation in group relatedness (mainly influenced by female relatedness) with roost characteristics contributing the most explained variation. This suggests that females using roosts of specific characteristics exhibit higher relatedness and seem to be philopatric. These females mate with more males than do more labile female groups. Results describe ecological and microevolutionary processes, which affect relatedness and social structure; findings are highly relevant to species distributions in both natural and human‐modified environments. Abstract : In this article, we combine information on roosting associations with genetic structure of Peter's tent‐roosting bats, Uroderma bilobatum to address how different kinds of environmental characteristics at different scales may be affecting stability of social groups.